Venice's most loyal city : civic identity in Renaissance Brescia - Bowd, Stephen D. (I Tatti studies in Italian Renaissance history., 2010)
For the past generation, most historical work on the Italian Renaissance has been devoted to the ways in which city states such as Venice transformed their captured territories into a regional state during the fifteenth century. The territorial state approach de-emphasizes the persistence of communal politics and the communal identities of the subject cities of the new territorial states. Bowd's study is an important corrective to this argument. Based on extensive archival research in Brescia and Venice, Venice's Most Loyal City explores the creation of a civic identity based on local politics, religion, and ritual. Communal identity flourished in Brescia in ways that reveal the strength of local autonomy and the limits of state building in the triumphal age for Venice. It is especially sophisticated in the analysis of the treatment of Brescia's Jews and alleged witches. By employing the most recent methods of historical analysis derived from ritual and religious studies, Bowd manages to return to an older conception of Renaissance Italy that has been eclipsed in recent years.